Fabrication of a novel PbO2 electrode with rare earth elements doping for p-nitrophenol degradation - Ke Wang; Xing, Xuan; Liu, Wen; Yi Jiang; Hongna Li; Yue Lu; Chen, Huiying; Huatang Ren (Journal of Environmental Chemical Engineering, 2023)
A novel PbO2 electrode modified with rare earth elements (La, Ce, Gd and Er) doping (named as Re-PbO2) was prepared by electrodeposition in the present study. The micro-morphology and crystal structure of Re-PbO2 were characterized by scanning electronic microscopy (SEM), energy dispersive spectroscope (EDS), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. Their electrochemical properties were determined by linear sweep voltammetry (LSV), cyclic voltammetry (CV), accelerated life test and hydroxyl radicals (•OH) formation analysis. Electrochemical oxidation of p-nitrophenol (p-NP) by Re-PbO2 compared with un-doped PbO2 has been investigated and the degradation rate followed the order of Er-PbO2 > Gd-PbO2 > La-PbO2 > Ce-PbO2 > PbO2. Especially for Er-PbO2, the pseudo-first order kinetic for p-NP (kp-NP) degradation was 0.41, which was only 0.19 for un-doped PbO2. Rare earths elements doping improved the oxidation ability of Re-PbO2 mainly through reducing grain size, increasing oxygen evolution potential, enlarging electrochemical active surface area and enhancing •OH formation ability. In addition, existing formation of oxygen species on PbO2 electrode surface was investigated by XPS. For Re-PbO2, percentage of lattice oxygen species (Oads) were higher than that on the un-doped one. These results demonstrated that rare earth elements can enhance the oxidation ability of PbO2 electrode significantly.
Keywords: Electrochemical oxidation; hydroxyl radicals; PbO Electrode; Rare Earth Elements